2019
DOI: 10.1093/nar/gkz026
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of the Fanconi anemia E2 ubiqitin conjugase UBE2T only partially abrogates Alu-mediated recombination in a new model of homology dependent recombination

Abstract: The primary function of the UBE2T ubiquitin conjugase is in the monoubiquitination of the FANCI-FANCD2 heterodimer, a central step in the Fanconi anemia (FA) pathway. Genetic inactivation of UBE2T is responsible for the phenotypes of FANCT patients; however, a FANCT patient carrying a maternal duplication and a paternal deletion in the UBE2T loci displayed normal peripheral blood counts and UBE2T protein levels in B-lymphoblast cell lines. To test whether reversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 129 publications
0
11
0
Order By: Relevance
“…“Cellular response to DNA damage stimulus” and “double-strand break repair” were among the mostly enriched ontology classes in both I-BET762- and I-BET762+TLZ-associated DEPs ( Figure 5 C). Among DEPs that are involved with DNA damage response, CHEK2, FANCC, NBN, OTUB1, UBE2B, and UBE2T have been reported to promote the HR-mediated DSBR process and they were down-regulated in both treatment groups [ 56 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] ( Figure S8 ). Furthermore, deficiencies in CHEK2, FANCC, or NBN have been shown to induce PARPi sensitivity in other tumor models [ 56 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…“Cellular response to DNA damage stimulus” and “double-strand break repair” were among the mostly enriched ontology classes in both I-BET762- and I-BET762+TLZ-associated DEPs ( Figure 5 C). Among DEPs that are involved with DNA damage response, CHEK2, FANCC, NBN, OTUB1, UBE2B, and UBE2T have been reported to promote the HR-mediated DSBR process and they were down-regulated in both treatment groups [ 56 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ] ( Figure S8 ). Furthermore, deficiencies in CHEK2, FANCC, or NBN have been shown to induce PARPi sensitivity in other tumor models [ 56 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous work in which the position of the I-Sce1 site was changed, we showed that homology directed repair that removes either the ectopic dTomato gene or the eGFP gene is 5 not inherently deleterious to cells (68). Therefore, the loss of the dTomato gene raised the possibility that the replication-dependent DSBs which were resistant to recombination and deleted all or part of chromosome 18 containing the dTomato gene were also inimical to cell survival.…”
Section: (Ctg/cag)n Repeat Length-dependent Dsbsmentioning
confidence: 99%
“…To identify factors affecting microsatellite DSBs and repair we developed a system in which a DSB between two chromosomal reporter genes could be detected by microscopy or flow cytometry ( Figure 1). In this system, (CTG/CAG)100 or (Pu/Py)88 microsatellites were individually integrated at a single copy FLP recombinase target (FRT) site at chromosome 18p11.22 in HeLa cells (64), bordered by the c-myc replication origin core (65)(66)(67), an I-Sce1 site, and two fluorescent protein marker genes (dTomato, eGFP) flanked by three identical AluYa5 elements ( Figure 1A) (68). Control cell lines were also constructed that contain the same starting construct except that the DF/myc cell line is missing the microsatellite sequences ( Figure 1B), and the DF cell line is additionally missing the c-myc origin core ( Figure 1C).…”
Section: A Dual Fluorescent Reporter System For Analysis Of Dna Dsbs mentioning
confidence: 99%
See 1 more Smart Citation
“…Ubiquitin signaling is a fundamental eukaryotic regulatory system, controlling diverse cellular functions, and once there are mutations or impairment of the E2 genes, severe disease states can occur [ 21 ]. Various studies reported that UBE2T influences tumors through the Fanconi anemia pathway [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%